2014
DOI: 10.1016/j.biomaterials.2013.11.065
|View full text |Cite
|
Sign up to set email alerts
|

The composition of tribofilms produced on metal-on-metal hip bearings

Abstract: Following wear testing in a hip simulator, the bearing surfaces of 36 mm metal on metal total hip replacements showed the formation of tribochemical layers. These layers were investigated in a transmission electron microscope, and analysis was performed using electron energy loss spectroscopy, energy dispersive x-rays and selected area electron diffraction. The tribofilm formed at the edge of the wear scar was 100 s of nanometres thick and contained cobalt sulphide particles embedded within. The film itself wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Here, we speculate and provide evidence that this could be related to the presence or absence of tribofilms. A ‘tribofilm’ is a carbonaceous layer or film (‘tribofilm’) that forms on the surfaces of MoM components [13–17]. We have recently reported that the film contains graphitic material [18], although this has yet to be independently confirmed [17].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we speculate and provide evidence that this could be related to the presence or absence of tribofilms. A ‘tribofilm’ is a carbonaceous layer or film (‘tribofilm’) that forms on the surfaces of MoM components [13–17]. We have recently reported that the film contains graphitic material [18], although this has yet to be independently confirmed [17].…”
Section: Introductionmentioning
confidence: 99%
“…These have been associated with an increase in interfacial hardness and the origin of nano-scale debris typically associated with Metal-on-Metal bearings [33,34]. Furthermore the changes in subsurface microstructure and tribo-chemical processes (chemical reactions owing to the tribological interactions) have been hypothesised to contribute to the overall degradation of sliding interfaces [35][36][37]. Zeng et al [32] has recently demonstrated decreases in wear depending upon the initial interfacial crystallinity.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Instead, it suggests that metal-organic composite-like layers are formed during the use of MoM bearings as a result of a tribochemical reaction. Recently, graphitic [25] and nongraphitic [41] carbon-rich tribological layers have been reported in studies of retrieved MoM bearings and MoM bearings subjected to hip simulators. In the present study, XPS analysis was performed to examine the chemistry of the nanocrystalline subsurface structure of the retrieved head.…”
Section: Resultsmentioning
confidence: 98%